Rehabilitation of critical land by Implementing complex agroforestry at the prioritized subwatersheds in the Muria Region - Maria Theresia Sri Budiastuti; Djoko Purnomo; Hendy Hendro; Untung Sudjianto; Budi Gunawan (Universitas Sebelas Maret, 2020)
The prioritized subwatersheds are comprised of seven subwatersheds that have been declared critical within the 52 subwatersheds in the Muria Mountains. An area of approximately 11,000 ha, the topography of the prioritized subwatersheds is wavy—the typical slope ranges from 25 to 45%—and susceptible to erosion. The purpose of this research was to evaluate agroforestry cropping patterns to support soil conservation and reclamation on critical lands. This study is a quantitative description of research conducted through survey. The results show that most of the researched area has Inceptisols soil type with sandy, clay, and loam textures. The nitrogen, phosphate, potassium, C-organic, and organic matter contents are relatively low while the vegetation Diversity Index is categorized as medium. Sengon trees dominate in the prioritized subwatersheds area, followed by mahogany, coffee, and teak with average Importance Values of 89.57, 60.24, 78.40, and 21.03, respectively. This research shows that an agroforestry system comprised of sengon trees and coffee is ideally applied in the prioritized subwatersheds. Coffee requires shade and reduces rain-induced erosion; sengon trees function as a shade while at the same time contributing to the soil as a source of nutrients. During rains, this combined agroforestry system is able to control surface runoff and soil erosion. A sengon/coffee-tree based agroforestry system is ecologically friendly and appropriate for development in the prioritized subwatersheds.